Effects of Moringa Leaf Extract (Moringaoleifera) in the Breastfeeding: Efek Pemberian Ekstrak Daun Kelor (Moringaoleifera) dalam Proses Menyusui - Septadina, Indri Seta; Murti, Krisna (Sriwijaya Journal of Medicine, 2018)
Exclusive breastfeeding for 6 months is a global strategies to promote the growth, development, health and survival of infants. Despite the many benefits of exclusive breastfeeding for infants, mothers, families and communities, the coverage is still low in many countries including Indonesia. Mother's milk is produced from the collaboration between mechanical stimulation of hormonal and nerve factors. One of the hormones that affects is the estrogen. The hormone estrogen is a sex hormone produced by the uterus to stimulate the growth of sex organs such as breasts and pubic hair and regulate the menstrual cycle. The hormone estrogen also plays a role to maintain the texture and function of the breast. Pregnancy in a woman, making the breast gland will be more developed by the influence of estrogen, somatomamotropin and prolactin hormones. The process is affected by the hormones estrogen and progesterone. Estrogen significantly stimulates the synthesis and release of pituitary hormone, this effect depends on the duration and dose of administration. In Indonesia, moringa plant is a local food that has the potential to be developed in culinary breastfeeding mothers because it contains phytosterol compounds that function to improve and facilitate the production of breast milk (laktogogum effect). This paper will discuss some of the facts about the effect of Moringaoleifera extract on prolactin levels in increasing the quantity and quality of breast milk in the breastfeeding process. The amount of nutrients in the Moringa leaf (Moringaoleifera) one such as phytosterol compounds (laktogogum effect) in increasing levels of pituitary hormone and iron hormones can have a positive impact on the health of the baby because breast milk is the most important and best natural baby food.